Species composition, density, gonad maturity stage and size of sea urchin at Wakatobi Archipelago, Southeast Sulawesi, Indonesia - Nurqadri Syaia Bakti; La Nane (Fisheries and Society Publisher, 2021)
Sea urchin is echinoderm that body surface is covered with the spines. Sea urchin gonad has been consumed along time by the people at Wakatobi Archipelago. Sea urhin species is worried will be degraded. On the other hand, there is no study on species composition, density, size and maturity stage of sea urchins on Tolandono Island and Sawa Island, Wakatobi Regency. The purpose of this study was to determine the species composition, abundance, size and maturity level of sea urchin gonads. Sea urchin density was calculated with a 10 × 10 m transect quadrate. The data was analyzed by descriptive qualitatively. The results showed that in Tolandono Island and Sawa Island there were 4 types of sea urchins, namely Tripneustes gratila, Echinotrix calamaris, Diadema setosum and Echinoemetra sp. The size of urchin Tripneustes gratilla is ranging between 2.5 cm and 8.5 cm with the density 2 Ind./100 m2. Meanwhile, the gonad maturation stage (TKG) of Tripneustes gratila is at a 4.8 cm and spawned at a size 8–8.5 cm. TKG I is in the size range of 4.8–5 cm, TKG II is at 5.9–6.2 cm, TKG III is 6.4–6.6 cm, TKG IV is 6.8–7.5 cm and TKG IV is 6.8–7.5 cm. V in size 8.5 cm.